2021
DOI: 10.1111/1471-0528.16661
|View full text |Cite
|
Sign up to set email alerts
|

Clinical validation of a new molecular test (Seegene Allplex™ Vaginitis) for the diagnosis of vaginitis: a cross‐sectional study

Abstract: Objective To validate the use of Seegene Allplex™ Vaginitis assay in the diagnosis of candidiasis, bacterial vaginosis (BV) and trichomoniasis. Design Cross‐sectional, prospective study conducted in a single centre. Setting Outpatient clinic of a gynaecology department. Population Consecutive symptomatic and asymptomatic women (18–60 years of age). Methods Comparison of the assay test with the reference standards for the diagnosis of vaginitis (cultures for yeasts, Nugent for BV and nucleic acid amplification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…A mixed vaginitis diagnosis is made according to the presence of symptoms, clinical findings and laboratory tests (Gram-staining, wet-mount smears, PCR tests and combination of point-of-care tests) ( Tempera et al., 2004 ). Some studies confirm that the presence of multiple vaginitis did not interfere with the assay performance ( Vieira-Baptista et al., 2021 ). The key points in diagnosing mixed vaginitis are as follows ( Sobel et al., 2013 ): an abnormal vaginal milieu and the simultaneous presence of at least two types of vaginitis.…”
Section: Diagnosis Of Mixed Vaginitismentioning
confidence: 96%
See 1 more Smart Citation
“…A mixed vaginitis diagnosis is made according to the presence of symptoms, clinical findings and laboratory tests (Gram-staining, wet-mount smears, PCR tests and combination of point-of-care tests) ( Tempera et al., 2004 ). Some studies confirm that the presence of multiple vaginitis did not interfere with the assay performance ( Vieira-Baptista et al., 2021 ). The key points in diagnosing mixed vaginitis are as follows ( Sobel et al., 2013 ): an abnormal vaginal milieu and the simultaneous presence of at least two types of vaginitis.…”
Section: Diagnosis Of Mixed Vaginitismentioning
confidence: 96%
“…The skill level of technicians is an influencing factor ( Nyirjesy et al., 2020 ). Recent research has shown that some new molecular assays (Affirm VPIII, Aptima, BD Max, Seegene Allplex) for the diagnosis of mixed vaginitis have performed well, identifying proportions ranging from 7.58% to 27.23% ( Schwebke et al., 2020 ; Vieira-Baptista et al., 2021 ).…”
Section: Epidemiologymentioning
confidence: 99%
“…These tests have also shown higher sensitivity than the original Amsel's test (92.7% vs. 75.6%; p < 0.0001) [9]. The recent results of a real-time multiplex PCR assay for bacterial vaginosis have a sensitivity of 91.7% and a specificity of 86.6%, compared to Nugent score and/or Amsel's criteria [10]. A previous study reported that sexually active women had a higher prevalence of bacterial vaginosis than the menopausal group, which is different from the results of this study [11].…”
Section: Discussionmentioning
confidence: 93%
“…25 Multiplex PCR tests, such as the Allplex Vaginitis, allow the concomitant diagnosis of other causes of vaginitis. 14 The sensitivity In the future, reports may include which bacteria are involved and even antibiotic resistance, as already happens in other clinical situations. 28 A combination with sexually transmitted infections (including HPV) may be a cost-effective option, allowing a full evaluation of the cervicovaginal milieu.…”
Section: Discussionmentioning
confidence: 99%
“…One sample was collected using a flocked swab for culture. 14 Measurement of the vaginal pH was performed using Macherey-Nagel pH strips (3.6-6.1) (Macherey-Nagel GmbH & Co. KG), applied directly to the vaginal wall. Whiff test was performed, adding a drop of 10% KOH to a sample of discharge.…”
Section: Materials S and Me Thodsmentioning
confidence: 99%